Pemberdayaan Petani Padi Sawah dalam Meningkatan Efisiensi Usaha Tani dengan Pembuatan dan Aplikasi Herbisida Organik di Desa Botolempangan Kabupaten Maros - Sri Muliani; Henny Poerwanty; Muhammad Kadir; Nildayanti Nildayanti; Adriani Adriani (Universitas 45 Surabaya, 2025)
Botolempangan Village in Bontoa Sub-district is one of the centers of paddy rice production in Maros Regency, with characteristics of rain-fed paddy fields that have many obstacles to weed infestation, especially if the dry season is abandoned from rice farming activities, before being planted during the rainy season where farmers are very dependent on the use of herbicides. Dependence on the use of synthetic (inorganic) herbicides occurs from the pre-growth period of seeds, seedlings to the maintenance process. High costs result in considerable inefficiencies in rice farming. Training in technology transfer efforts to make Organic Herbicide Formulations, and their applications are carried out to increase the Empowerment and Efficiency of rice farming on Rainfed Rice Fields. With the efficiency target is to increase the profit of paddy rice farming, minimizing inorganic herbicide inputs. The output of this activity ultimately produces products that can be applied to at least reduce or reduce the use of inorganic herbicides. At the end of the activity, farmer business groups are able to produce and apply Organic Herbicide Formulations on Demoplots on Farmer-Owned Land.